A63 HOSPITALIZATION RATES FOR INFLAMMATORY BOWEL DISEASE VARY GEOGRAPHICALLY IN SOUTHERN ALBERTA: A POPULATION-BASED COHORT STUDY. (26th February 2020) - Stach, J; Coward, S; Charette, J H; Jelinski, S; van Zanten, S; Morrin, L; Kroeker, K; Baumgart, D; Seow, C; Panaccione, R; Novak, K L; Kaplan, G G
Abstract: Background: Hospitalization rates for patients with inflammatory bowel disease (IBD) are decreasing throughout Canada; however, this may vary across Canadian jurisdictions. Access to gastroenterologists is limited in many parts of Canada, resulting in care by non-gastroenterologists, and variation in outcomes. Aims: To assess trends of hospitalization rates in three regions in Southern Alberta: Calgary zone, a metropolitan city; Chinook region: local gastroenterologists; and Palliser region: no local gastroenterologists. Methods: The Alberta IBD Surveillance Cohort is a population-based database consisting of an algorithmically defined prevalent IBD population for Alberta. IBD patients in Southern Alberta were identified by 3-digit postal code and their hospitalizations from the Discharge Administrative Database were extracted (2002 to 2015). IBD patients were stratified by the number of IBD prevalent patients: Calgary Zone (n=9625 in 2015), Palliser region (n=1419), and Chinook region (n=727). Age- and sex- standardized hospitalization rates, per 100 prevalent IBD patients, were calculated for each year. Average Annual Percentage Change (AAPC with associated 95% confidence intervals (CI)) were calculated using the log-linear regression. Rate ratios of standardized hospitalization rates between Calgary, Chinook, and Palliser were calculated. Results: From 2002 to 2015 the average hospitalization rate (per 100 prevalent population) was: 27.6 in Calgary, 30.2 in Chinook, and 37.4 in Palliser (Table 1). The AAPCs across these regions were significantly decreasing (Figure 1). By 2011–2015 hospitalization rates fell to 23, 26.3, and 30.2 in Calgary, Chinook, and Palliser, respectively (Table 1). Calgary and Chinook had significantly lower hospitalization rates compared to Palliser (Calgary: 0.72, 95% CI: 0.70, 0.75; Chinook: 0.80, 95% CI: 0.76, 0.84) (Table 1). Conclusions: Hospitalization rates for patients with IBD are decreasing, which may be explained by advances in therapeutic modalities and increased expertise of gastroenterologists. The lack of access to a local gastroenterologist in Palliser may account for higher hospitalization rates for patients with IBD. Future studies are needed. Funding Agencies: CIHRDHSCN (Digestive Health Strategic Clinical Network), AHS (Alberta Health Services)